Current Approaches to the Treatment of Endometriosis: A Narrative Review - Słowik, Justyna; Mika , Wiktoria; Sieradzka, Izabela; Wajda, Katarzyna; Kostyniak, Wiktoria (Journal of Education, Health and Sport, 2026)
Endometriosis is a complex, systemic clinical syndrome affecting over 10% of women and significantly impairing reproductive function and quality of life. Common symptoms include pelvic pain, dysmenorrhea, dyspareunia, and abnormal menstrual bleeding, often resulting in surgical interventions and, historically, hysterectomy [1]. The pathogenesis of endometriosis is multifactorial, involving hormonal imbalance, chronic inflammation, and genetic and epigenetic factors. While retrograde menstruation remains the most accepted mechanism, other processes, such as coelomic metaplasia, stem cell involvement, and immune dysregulation, contribute to ectopic endometrial tissue implantation and persistence [2]. Epigenetic modifications further affect gene expression and hormonal responsiveness, promoting disease progression. Diagnosis combines clinical evaluation and imaging, with laparoscopy and histological confirmation as the gold standard. Less invasive techniques, such as transvaginal ultrasound and MRI, are increasingly used due to their sensitivity for detecting deep lesions [4]. Treatment is tailored to symptom severity, disease extent, and fertility goals, integrating pharmacological, surgical, and supportive methods. Hormonal therapies such as combined oral contraceptives, progestins, and GnRH analogues, are first-line treatments, while surgery is reserved for refractory cases or anatomical complications. [3] Complementary interventions—such as physical activity, physiotherapy, dietary modifications, and psychological support—can enhance symptom control and quality of life.[4] Comprehensive, multidisciplinary care is essential to optimize emphasizing early diagnosis, individualized therapy, and supportive care.